Nitrogen application forms in different stages of soy culture development - Pereira, C. S.; Sanchez, J. V. (Scientific Electronic Archives, 2020)
In Brazil, inoculation with Bradyrhizobium japonicum strains is the main form of N assimilation by soybeans, but there are reports of the use of mineral N as a complement to the demand of this nutrient by the plant. The objective of this work was to verify the effect of different forms and times of N application on vegetative growth and soybean crop yield in northern Mato Grosso. The experimental design was a randomized block design (DBC) with 10 treatments: control (no N application); and in all other treatments 10 kg ha-1 of N was applied, changing season and form of application as: the haul in cover at planting; in V2 at hedging; in V2 via leaf; in V4 at hedging; of N in leaf V4; from N in R1 to hedging; N in leaf R1; in R2 at cover and in R2 leaf. The cultivar used was Bonus from BrasmaxÂ®. Vegetative growth was evaluated by height, stem diameter, shoot dry mass, nodulation by number of nodules and yield by variables, number of pods, grains per pod, mass of 1000 grains, and weight. productivity. In practically all variables analyzed, no effects of nitrogen application on soybean crop were verified. The shoot dry mass was higher when nitrogen was applied to V2 via foliar spraying and to V4 in soil cover. In general, although there was no statistical difference between treatments, N application at the beginning of crop development increased soybean yield. The application treatment V2 was the most productive, produced 34% more than the control without N, or 17.34 more bags than the control.